Editorial - Katherine Bullock (International Institute of Islamic Thought, 2006)
As if to give the lie to my last editorial, in which I argued that the “war on terror” was a smokescreen covering the imperial ambitions of the United States’ neo-conservative political elite, on the day that the issue went to press, Toronto’s Royal Canadian Mounted Police (RCMP) announced the arrest of seventeen young Muslim men on terrorism-related charges. Five are under 18, several are over 30, and the rest are in their late teens and early 20s. The shock permeated Toronto. Non-Muslims were shocked that “it could happen here,” and Muslims were shocked that some of their own were willing to kill fellow Canadians. As can be imagined, the following media frenzy displayed the usual racism (disguised as attacks on multiculturalism) from commentaries, editorials, letters to the editor, and experts concerning the “threat” of Muslim extremism in Canada. Muslim organizations and those with links to the media were back on the media circuit (or is it circus?) doing interviews, hot on the heels of the cartoon controversy, trying to explain this and to distance themselves and Islam as a religion from attack. There was the usual spike in Islamophobic backlash, although this was largely contained by Toronto’s Mayor David Miller and other leaders. There was also the usual skepticism and claims of anti-Muslim discrimination from some Muslims. While we do not know the veracity of the evidence, and while it may be admirable that the belief is so strong that Islam prohibits terror that we cannot conceive of fellow Muslims doing such a thing, it ultimately harms the community that this kind of response is so widespread. For one thing, the media use this sentiment to mock us and portray us as cold and indifferent to the threat of terror. For another, although it seems to be painful for some to admit, our community has to take ownership of the extremism existing in its midst. These men may be innocent and may have been framed or discriminated against, but we have to face up to the results of such extremist interpretations. It is all very well to say that “this is not Islam” and to worry about the media’s portrayal of Islam as a religion of violence, but we must also talk to ourselves and our youths and show them that such actions are beyond the pale of Islam. Moreover, we need to debunk the arguments of those Muslims who challenge this view ...